The Internet as a Tool to Improve the Teaching and Learning Process at Universidad de Managua - Mesa Cornavata, Doris María (2019)
The research context of this article proposes a strategy to develop the use of information and communication techniques (ICT) that will support the Teaching and learning process in order to achieve its relevance and usefulness in education at the University of Managua (UdeM). This institution has invested in technological infrastructure; however, it is perceived that students do not always make proper use of it to improve their academic performance. A significant percentage use ICT as a distraction element as evidenced by direct observation and data statistics generated in the technological centers, hence the importance of diagnosing the use of the Internet by students of UdeM. The main results show that the use of the Internet as a complementary element is a valid option for UdeM students since 73.5% have access to a computer at home, 65.3% have Internet access at home, and 41.8% have Internet access through their cell phones.